(untitled) (Al-Aasar, 2025)
This study investigates the challenges of tacit knowledge management and the influence of disruptive technologies at the university level. It examines the defining characteristics, management practices, philosophical and practical issues, technological constraints, and strategies for operationalizing tacit knowledge. The objectives include analyzing tacit knowledge features and management at universities, exploring philosophical and practical challenges, addressing technological and IT-related issues, and identifying research gaps. Using a sample of 100 teachers from Higher Education Commission-recognized universities in Punjab, Pakistan, the study employs a three-point rating scale developed from a literature review. Data analysis reveals general agreement on the complexity of tacit knowledge and its management, with notable issues in IT-related challenges. The study concludes that while tacit knowledge is deeply embedded and difficult to transfer, the role of technology remains crucial yet limited, necessitating more tailored solutions for effective knowledge sharing and operationalization.